1956
DOI: 10.1039/jr9560003953
|View full text |Cite
|
Sign up to set email alerts
|

770. The gum component of olibanum

Abstract: Two polysaaccharides designated I and I1 have been isolated from the gum component of olibanum, the gum oleoresin from Boswellia carteri. Polysaccharide I is neutral and composed of galactose and arabinose in equimolecular ratio. Polysaccharide I1 is acidic and composed of galactose and galacturonic acid in the molar ratio 2 : 1. OLIBANUM, the gum oleoresin exuded from the incense tree Boswellia, has been extensively studied. Most of the work dealt with the chemistry of its resin and its essential oils and lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1960
1960
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(315) were not found to be the same ( 19% for B. papyrifera, 32% for B. carteri). Methylation analysis of two fractions from B. carteri gum showed that both contain a branched galactan molecular framework (317). Gum myrrh from damaged bark of Commiphora myrrha is a mixture of chemical components, from which a polysac charide ([α] Ό -32°) can be isolated with some difficulty because of its association with protein (318).…”
Section: The Contribution Of the Glucuronomannoglycan Chain To The Momentioning
confidence: 99%
“…(315) were not found to be the same ( 19% for B. papyrifera, 32% for B. carteri). Methylation analysis of two fractions from B. carteri gum showed that both contain a branched galactan molecular framework (317). Gum myrrh from damaged bark of Commiphora myrrha is a mixture of chemical components, from which a polysac charide ([α] Ό -32°) can be isolated with some difficulty because of its association with protein (318).…”
Section: The Contribution Of the Glucuronomannoglycan Chain To The Momentioning
confidence: 99%